The in vivo role of PtdIns(3,4,5)P(3) binding to PDK1 PH domain defined by knockin mutation - McManus, Edward J (2004)
We generated homozygous knockin ES cells expressing a form of 3-phosphoinositide-dependent protein kinase-1 (PDK1) with a mutation in its pleckstrin homology (PH) domain that abolishes phosphatidylinositol 3,4,5-tris-phosphate (PtdIns(3,4,5)P(3)) binding, without affecting catalytic activity. In the knockin cells, protein kinase B (PKB) was not activated by IGF1, whereas ribosomal S6 kinase (RSK) was activated normally, indicating that PtdIns(3,4,5)P(3) binding to PDK1 is required for PKB but not RSK activation. Interestingly, amino acids and Rheb, but not IGF1, activated S6K in the knockin cells, supporting the idea that PtdIns(3,4,5)P(3) stimulates S6K through PKB-mediated activation of Rheb. Employing PDK1 knockin cells in which either the PtdIns(3,4,5)P(3) binding or substrate-docking ‘PIF pocket' was disrupted, we established the roles that these domains play in regulating phosphorylation and stabilisation of protein kinase C isoforms. Moreover, mouse PDK1 knockin embryos in which either the PH domain or PIF pocket was disrupted died displaying differing phenotypes between E10.5 and E11.5. Although PDK1 plays roles in regulating cell size, cells derived from PH domain or PIF pocket knockin embryos were of normal size. These experiments establish the roles of the PDK1 regulatory domains and illustrate the power of knockin technology to probe the physiological function of protein–lipid and protein–protein interactions.